2015
DOI: 10.1021/am508579r
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional AlPO4 Coating for Improving Electrochemical Properties of Low-Cost Li[Li0.2Fe0.1Ni0.15Mn0.55]O2 Cathode Materials for Lithium-Ion Batteries

Abstract: Layered Li-rich, Fe- and Mn-based cathode material, Li[Li0.2Fe0.1Ni0.15Mn0.55]O2, has been successfully synthesized by a coprecipitation method and further modified with different coating amounts of AlPO4 (3, 5, and 7 wt %). The effects of AlPO4 coating on the structure, morphology and electrochemical properties of these materials are investigated systematically. XRD results show that the pristine sample is obtained with typical Li-rich layered structure and trace amount of Li3PO4 phase are observed for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(90 citation statements)
references
References 44 publications
3
87
0
Order By: Relevance
“…That is why, surface coatings with Al 2 O 3 , AlF 3 , AlPO 4 , MgO, with a novel surface configuration of Mg 3 (PO 4 ) 2 or effective modification by Li 2 MnO 3 which suppress layered-to-spinel transitions can stabilize capacity and voltage decay upon prolonged cycling of Li-, Mn-rich cathodes. [60][61][62][63][64][65] Similar results were obtained by doping of these cathodes with foreign cations (Na, Mg, Al, Zr, etc.) as described below.…”
Section: Efforts To Reduce Capacity Fading and Discharge Voltage Decasupporting
confidence: 70%
See 1 more Smart Citation
“…That is why, surface coatings with Al 2 O 3 , AlF 3 , AlPO 4 , MgO, with a novel surface configuration of Mg 3 (PO 4 ) 2 or effective modification by Li 2 MnO 3 which suppress layered-to-spinel transitions can stabilize capacity and voltage decay upon prolonged cycling of Li-, Mn-rich cathodes. [60][61][62][63][64][65] Similar results were obtained by doping of these cathodes with foreign cations (Na, Mg, Al, Zr, etc.) as described below.…”
Section: Efforts To Reduce Capacity Fading and Discharge Voltage Decasupporting
confidence: 70%
“…[61] Wu et al reported that 5 wt% of AlPO 4 exhibited the best cyclic performance (74.4% capacity retention after 50 cycles) due to suppression of surface side reactions and diffusion of oxygen vacancies and acceleration of Li-ion transport. [63] Composite materials of Li-, Mn-rich oxides with high voltage spinel were found to stabilize the layered structure and suppress the layered-to-spinel transformation, thus improving the A schematic presentation of layered-to-spinel transformation of rhombohedral and monoclinic components of a layered-layered cathode material. Reproduced with permission.…”
Section: Efforts To Reduce Capacity Fading and Discharge Voltage Decamentioning
confidence: 99%
“…2017, 7, 1601284 www.advenergymat.de www.advancedsciencenews.com initial layered structure to spinel phase, which facilitates the Li + ion conduction and improves the rate performance of the LMR cathode Li [Li 0.19 Ni 0.16 Co 0.08 Mn 0.57 ]O 2 . From this perspective, other surface coatings or modifications that could stabilize the electrode/electrolyte interface have been repeatedly reported to enhance the rate performance of LMR cathodes, such as Al 2 O 3 , [94] FePO 4 , [95] Pr 6 O 11 , [96] AlPO 4 , [97] F-doped SnO 2 (FTO), [98] Li 2 O-LiBO 2 -Li 3 BO 3 glass coating, [99] MnO 2 modification, [100] and so on. From this perspective, other surface coatings or modifications that could stabilize the electrode/electrolyte interface have been repeatedly reported to enhance the rate performance of LMR cathodes, such as Al 2 O 3 , [94] FePO 4 , [95] Pr 6 O 11 , [96] AlPO 4 , [97] F-doped SnO 2 (FTO), [98] Li 2 O-LiBO 2 -Li 3 BO 3 glass coating, [99] MnO 2 modification, [100] and so on.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…Various effective methods have been adopted to solve these critical problems via coatings of sundry materials [9][10][11][12][13], such as metal oxides [14,15], metal phosphates [16,17], and metal fluorides [18]. A proper coating layer can defend the electrode surface from direct contact with the electrolyte and reduce the side-reactions between the electrolyte and electrode [19,20].…”
Section: Introductionmentioning
confidence: 99%